Fibroblast Growth Factor 2 Attenuates Renal Ischemia-Reperfusion Injury via Inhibition of Endoplasmic Reticulum Stress - Tan, Xiaohua; Tao, Qianyu; Li, Guixiu; Xiang, Lijun; Zheng, Xiaomeng; Zhang, Tianzhen; Wu, Cuijiao; Li, Dequan (Frontiers in Cell and Developmental Biology, 2020)
Acute kidney injury (AKI) is a serious clinical disease that is mainly caused by renal ischemia-reperfusion (I/R) injury, sepsis, and nephrotoxic drugs. The pathologic mechanism of AKI is very complex and may involve oxidative stress, inflammatory response, autophagy, apoptosis, and endoplasmic reticulum (ER) stress. The basic fibroblast growth factor (FGF2) is a canonic member of the FGF family that plays a crucial role in various cellular processes, including organ development, wound healing, and tissue regeneration. However, few studies have reported the potential therapeutic effect of FGF2 in the repair of renal ischemic injury in the past two decades. In the present study, we investigated the protective effect of FGF2 on renal I/R injury using Sprague-Dawley and NRK-52E cells. Our results showed that FGF2 significantly attenuates the apoptosis of kidney tissues after I/R injury through the inhibition of excessive ER stress. Moreover, FGF2 also alleviated the excessive ER stress and apoptosis in cultured NRK-52E cells injured by tert-Butyl hydroperoxide (TBHP). Significantly, phosphatidylinositol 3-kinase (PI3K)-selective inhibitor LY294002 and mitogen-activated protein kinase kinase (MEK)-selective inhibitor U0126 were utilized in the present study to examine the protective mechanism of FGF2. Our in vitro experimental results confirmed that both LY294002 and U0126 largely abolished the protective effect of FGF2. Taken together, the findings of the present study indicated that FGF2 attenuates I/R-induced renal epithelial apoptosis by suppressing excessive ER stress via the activation of the PI3K/AKT and MEK-ERK1/2 signaling pathways.